Source and sink carbon dynamics and carbon allocation in the Amazon basin. Issue 5 (25th May 2015) - Doughty, Christopher E.; Metcalfe, D. B.; Girardin, C. A. J.; Amezquita, F. F.; Durand, L.; Huaraca Huasco, W.; Silva‐Espejo, J. E.; Araujo‐Murakami, A.; da Costa, M. C.; da Costa, A. C. L.; Rocha, W.; Meir, P.; et al.
Abstract Changes to the carbon cycle in tropical forests could affect global climate, but predicting such changes has been previously limited by lack of field‐based data. Here we show seasonal cycles of the complete carbon cycle for 14, 1 ha intensive carbon cycling plots which we separate into three regions: humid lowland, highlands, and dry lowlands. Our data highlight three trends: (1) there is differing seasonality of total net primary productivity (NPP) with the highlands and dry lowlands peaking in the dry season and the humid lowland sites peaking in the wet season, (2) seasonal reductions in wood NPP are not driven by reductions in total NPP but by carbon during the dry season being preferentially allocated toward either roots or canopy NPP, and (3) there is a temporal decoupling between total photosynthesis and total carbon usage (plant carbon expenditure). This decoupling indicates the presence of nonstructural carbohydrates which may allow growth and carbon to be allocated when it is most ecologically beneficial rather than when it is most environmentally available.